2019
DOI: 10.12659/msm.915487
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mRNA Expression and Endogenous RNA Profiles in Bladder Cancer Based on The Cancer Genome Atlas (TCGA) Database

Abstract: Background Bladder cancer is a multifactorial disease with increasing incidence and mortality. Genetic alterations and altered expressions of mRNAs, long non-coding RNAs (lncRNAs), and miRNAs have been shown to play important roles in the tumorigenesis of bladder cancer. However, the functions of key RNAs and their regulatory network in bladder cancer are still to be elucidated. Material/Methods RNA profiles were downloaded from The Cancer Genome Atlas (TCGA) database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…Chu et al (2018)[40]30.615/ n = 407NA/ NA7ZNF230; BCL2L14; AHNAK; TMEM109; APOL2; AGER; AOC2Z. Xu et al (2019)[41]NA0.735/ n = 412NA/ NA11MXRA7; EMP1; TNFA1P8L3; SERPINB12; SAPCD1; GABRG1; PLEKHG4B; ABCA4; PTPRR; XAGE2; PEX5LNote: NA represents “not available”, Ref. represents References…”
Section: Resultsmentioning
confidence: 99%
“…Chu et al (2018)[40]30.615/ n = 407NA/ NA7ZNF230; BCL2L14; AHNAK; TMEM109; APOL2; AGER; AOC2Z. Xu et al (2019)[41]NA0.735/ n = 412NA/ NA11MXRA7; EMP1; TNFA1P8L3; SERPINB12; SAPCD1; GABRG1; PLEKHG4B; ABCA4; PTPRR; XAGE2; PEX5LNote: NA represents “not available”, Ref. represents References…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of the expression profiles of lncRNAs in HNSCC cells from the Cancer RNA-Seq Nexus (CRN) database have shown that the expression of LINC00460 is upregulated [14, 15]. Located on chromosome 13q33.2 and transcribed as a 913-nt transcript, LINC00460 has been reported to play important roles in tumorigenesis and progression in various tumors and is significantly correlated with survival in the context of several cancer types, including lung cancer [1619], esophageal cancer [2022], colorectal cancer [23, 24], nasopharyngeal carcinoma [25], papillary thyroid carcinoma [26], ovarian cancer [27], gastric cancer [28, 29], renal carcinoma [30], meningioma [31], and bladder and urothelial carcinoma [32, 33] . According to previous studies, LINC00460 exhibits aberrant expression in and may directly participate in the pathogenesis of HNSCC [13, 34, 35].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 14 genes were screened and the corresponding gene families were annotated in accordance with the human gene classification in the HGNC database 43 . Moreover, GO enrichment analyses were carried out using these 14 prognosis-specific immune-related genes and clusterProfile 44 of R package.…”
Section: Methodsmentioning
confidence: 99%